Evaluation on the Efficacy of Synthetic insecticides for the Management of Fall Armyworm, Spodoptera frugiperda (J.E. Smith (Lepidoptera: Noctuidae) in Maize - Sharma, Sheela; Thapa, Resham Bahadur; Pokhrel, Suroj; Neupane, Saraswoti; Tiwari, Sundar; Adhikari, Chiran (Journal of the Plant Protection Society, 2023)
Fall armyworm, Spodoptera frugiperda is an invasive and notorious pest of maize in many countries including Nepal. Several approaches of integrated management have been adopted for its control, chemical being the most popular choice in the farmers’ fields. Efficacy of such chemical pesticides for fall armyworm is interpreted as per the location, season, time and crops. In some cases, insect pests are always increasing the pesticide resistance. Hence to minimize the confusion of insecticide efficiency in various levels of understanding in the farmers’ level, field research was conducted in October 2021 to April, 2022. Seven different treatments (azadirachtin, chlorantraniliprole, emamectin benzoate, spinosad, spinetoram, imidacloprid and control) were tested in a four replicated RCBD design. Two sprays were made in twenty-days after seeding and fifteen-days after first spray in openfield condition. Minimum damage across various stages of maize plant was recorded inspinosad sprayed plots followed by spinetoram, chlorantraniliprole and emamectin benzoate, respectively. Maize yield was also recorded highest in spinosad and spinetoram sprayed plots. Highest score of damage was recorded in imidacloprid treated plots. This study further proved spinosad and spinetoram are the most popularly applied insecticides for the fall armyworm management.